ANALYSIS AND IMPLEMENTATION OF COMPUTER NETWORK SYSTEMS USING SOFTWARE DRAW.IO - Hendrawan, Eko; Meisel, Michael; Sari, Dita Novita (Asia Information System Journal, 2023)
Computer Networks Refers To Computing Devices That Are Connected And Can Exchange Data And Share Resources With. These Network Devices Use A System Of Rules, Known As A Communication Protocol, To Transmit Information Via Physical Or Wireless Technology. Two Computers Can Be Said To Be Connected In A Network If Both Have The Ability To Communicate And Exchange Information. The Author Chooses A Place At The Patria Gadingrejo Pringsewu Senior High School, Lampung. Computer Network Implementation Using Star Topology. In This Paper, A Computer Network Is Simulated At Patria Gadingrejo Pringsewu High School, Lampung, INDONESIA. Using Draw.Io Software As A Simulation Tool. Simulation Data Obtained From Computer And Network Engineering Laboratory Room, Accounting Laboratory Room And General Laboratory Room. Each Laboratory Room Has 1 Switch And 1 Wireless Router. The Performance Analyzed Is Packet Loss, Delay And Throughput. The Simulation Results Using Draw.Io Software Show That The Delay That Occurs In The Computer And Network Engineering Laboratory Is 30.4 Ms, The Accounting Laboratory Is 43.4 Ms And The General Laboratory Is 50.2 Ms. While The Entire Room Does Not Experience Packet Loss During The Simulation Process. The Throughput Results For TKJ-Laboratory Rooms Are 0.51 kbps, For Akuntansi-Laboratory Rooms Are 0.38 Kbps And for general Laboratory Rooms Are 0.37 kbps.